2005
DOI: 10.1097/01202412-200507000-00011
|View full text |Cite
|
Sign up to set email alerts
|

The vertical expandable prosthetic titanium rib implant for the treatment of thoracic insufficiency syndrome associated with congenital and neuromuscular scoliosis in young children

Abstract: Expansion thoracoplasty and vertical expandable prosthetic titanium rib (VEPTR; Synthes Spine Co., West Chester, Pennsylvania, USA) implantation is a new method for the treatment of thoracic insufficiency syndrome and congenital spinal deformity in children. The longitudinal rib implant expands the thorax and indirectly corrects spinal deformity, thus allowing spinal, thoracic and probably lung growth. VEPTR has been used since 1989 in San Antonio, USA, and was introduced to Europe in 2002. This paper describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
65
0
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(71 citation statements)
references
References 14 publications
0
65
0
6
Order By: Relevance
“…The literature supports the use of both techniques but also documents complications in this population including proximal migration of devices with rib fractures, and skin problems secondary to recurrent surgery and hardware [3,8,10,13]. The complication rates ranged from 8% to 50% [2,3,8,10,13]. The literature also suggests the growing rod systems are associated with a high complication rate (ie, 8% to 50%) with the majority being minor; these systems appear to halt curve progression but not reduce curve magnitude [10,13].…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations
“…The literature supports the use of both techniques but also documents complications in this population including proximal migration of devices with rib fractures, and skin problems secondary to recurrent surgery and hardware [3,8,10,13]. The complication rates ranged from 8% to 50% [2,3,8,10,13]. The literature also suggests the growing rod systems are associated with a high complication rate (ie, 8% to 50%) with the majority being minor; these systems appear to halt curve progression but not reduce curve magnitude [10,13].…”
Section: Introductionmentioning
confidence: 76%
“…Growing rods [7] and the Vertical Expandable Prosthetic Titanium Rib (VEPTR TM ; Synthes Spine Co, West Chester, PA) [8] are commonly used to treat EOS. The literature supports the use of both techniques but also documents complications in this population including proximal migration of devices with rib fractures, and skin problems secondary to recurrent surgery and hardware [3,8,10,13]. The complication rates ranged from 8% to 50% [2,3,8,10,13].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hell et al [12] reported three complications encompassing 15 primary VEPTR implantations. These included rib fracture, lumbar hook displacement, and skin breakdown.…”
Section: Discussionmentioning
confidence: 99%